HRM Practices and how they Effect on Employees’ Job Performance: Proof from Two Institutional Frameworks in Uttar Pradesh - Jyoti Soni, Vipin Kumar (Journal of Daoist Studies, 2026)
The study evaluates the effects of performance evaluation, training and development, and hiring and selection on employees' job performance. The government and self-financed institutions in Uttar Pradesh are the two different institutions in which the proposed study assesses HRM practices. Using random sampling method, the sample data of 400 employees (teaching/non-teaching staff) was collected from Government and self – financed institutions of Uttar Pradesh using questionnaire method. The data was analyzed using descriptive and inferential statistical methods like correlational analysis and the t-test. As stated by the study, there isn’t a strong correlation between any of the HRM techniques applied in the study area and both teaching and non-teaching employees. Nonetheless, it was also discovered that there are no appreciable distinctions between government and self-financed institutions performance appraisal practices. This will show that general HRM practices have a substantial effect on teaching and non-teaching employee members' job performance in both government and self-financed institutions. The study's limits are revealed, recommendations for high-performance HR practices and employees' job performance are offered, and future research prospects for academics are highlighted.